Case report: Child chronic nonbacterial osteomyelitis with rapid progressive scoliosis-an association with disease? - Shi, Xiaojun; Hou, Xiujuan; Hua, Haiqin; Dong, Xia; Liu, Xiaoping; Cao, Fengjiao; Li, Chen (Frontiers in Pediatrics, 2023)
Background: Chronic nonbacterial osteomyelitis (CNO) is an auto-inflammatory bone disease that usually develops in childhood. Spinal involvement is a common manifestation of CNO, but it is rare for CNO to lead to rapid progression of scoliosis deformity. Here we present a 9-year-old girl with acute scoliosis with CNO and scoliosis progressed rapidly in 2 months. Case Presentation: A 9-year-old girl presented bilateral shoulder inequality with pain in the left hypochondrium for 2 months. Standing spinal X-rays showed right convex scoliosis with a 25° Cobb angle. Chest magnetic resonance imaging (MRI) showed that the T8 vertebra was flattened and local bone was destroyed with bone marrow edema. The bone biopsy showed evidence of fibrosis and chronic inflammatory changes with no specific diagnosis. One month later, her scoliosis and bone destruction deteriorated obviously. Thoracic vertebra MRI showed that the T8 vertebra had a compression fracture. 99mTc-MDP whole-body bone scintigraphy showed intense uptake at T8/9 and the right sacroiliac joint. She was diagnosed with CNO accompanied by rapidly progressive scoliosis. The scoliosis was successfully treated with adalimumab and zoledronic acid, which showed significant improvement after 6 months of follow-up. Conclusion: Zoledronic acid and adalimumab successfully treated CNO with rapidly progressive scoliosis, but could not prevent vertebral compression.